Financial Policy Implementation at the Ministry of Research and Development Institutions During the COVID-19 Pandemic - Permatasari, Avinda; Septiani, Maretin Dwikurnia (KnE Social Sciences, 2022)
At the end of 2019, an outbreak of COVID-19 occurred in China. Soon after, a global pandemic was declared. The virus entered Indonesia. The increase in COVID-19 cases led to reduced national economic growth, decreased state revenues, and increased state spending and financing. There were three significant impacts, namely on purchasing power, weakening investment, and declining export commodities. This changed the direction of Indonesia’s financial policy. Quick steps were taken by the Government to help overcome the COVID-19 pandemic, namely by refocusing the budget to deal with the pandemic. This policy resulted in capital expenditure for projects and research that were not directly related to the COVID-19 response to be postponed. Moreover, some activities or projects that had been contracted had to be renegotiated to delay work, and employee spending had to be postponed as well. The purpose of this research was to analyze the impact of the changes in Government economic policies outlined in the Medium-Term Development Plan (RPJM) on the field of research and development, and to analyze potential research and development in the field of technology that can be carried out in dealing with the pandemic. This work was conducted using descriptive qualitative methods, and data were collected through interviews and direct observations. Keywords: COVID-19, economic policy, budget refocusing